Trade facilitation in southern Africa : a case study for Zimbabwe - Mureverwi, Brian (GSB: Faculty, 2016)
The recent adoption of the Trade Facilitation Agreement by WTO members in 2014 renewed the global impetus to ease the movement of goods. Developing countries in Sub Saharan Africa have joined the global community in this regard. It has been noted that although tariffs in developing countries have been lowered, numerous non-tariff barriers and non-tariff measures are stifling trade. Cumbersome border processes have added avoidable costs to trade. In this study, we examine the challenges being faced in Zimbabwe in the transboundary movement of goods. The study makes use the World Bank database on Trading Across Border, Logistics Performance Indicators, and the Ad Valorem Equivalent by the World Bank's Economic and Social Community for Asia and Pacific. The data is compared with South Africa, Zambia, OECD High Income Countries, and East Asia. The findings show that, it is a huge challenge to move goods in Zimbabwe. In other words, doing business with Zimbabwe is not for the faint at heart. These challenges emanate from exorbitant administrative fees, high document requirements, and time delay constraints. These costly non-tariff barriers present a costly murky trade protectionism. The entire logistics chain and infrastructure system need to be revamped to improve reliability and minimise trade costs. When compared to ad valorem equivalent, Zimbabwe trade costs with South Africa and Zambia in agriculture are in excess of 100%, while those for the manufactured goods average 65%. The high trade costs in agriculture are high mainly due to excess requirements in terms of processes and procedures to move goods across borders. Combining trade costs data with specific knowledge on trade facilitation, logistics and trade policy will provide a comprehensive diagnosis that will help to prioritize reform packages that carry maximum impact. In light of these findings, the research recommends to customs officials and government policy makers, areas to address in the entire trade facilitation process that will bring huge impact in terms of removal of border inefficiencies, minimising of trade costs, and improvement of the logistics chain. These recommendations range from the establishment of single window system, integrated border management, and one stop border posts as part of the entire process under trade facilitation.